Sertifikat Sebagai Alat Pembuktian Yang Kuat Dalam Hubungannya Dengan Sistem Publikasi Pendaftaran Tanah - Arifin Bur; Desi Apriani (UIR Press, 2017)
The assurance of legal certainty over the control of land rights is very urgent, especially in the current state of the state. For this reason the government regulates the registration of land in the Basic Agrarian Law and Government Regulation Number 24 of 1997 on Land Registration. With the registration of land rights, the right holder obtains the certificate as a strong evidence. In this regard, the negative publication system is embraced in a land registration system that aims to protect the true rights holder. However, on the other hand the land registration publication system in Indonesia also contains positive elements as seen in the provisions of Article 32 paragraph (2) PP. No. 24 of 1997 on Land Registry.